3x-2(-2)=13

Simple and best practice solution for 3x-2(-2)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2(-2)=13 equation:


Simplifying
3x + -2(-2) = 13

Multiply -2 * -2
3x + 4 = 13

Reorder the terms:
4 + 3x = 13

Solving
4 + 3x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 3x = 13 + -4

Combine like terms: 4 + -4 = 0
0 + 3x = 13 + -4
3x = 13 + -4

Combine like terms: 13 + -4 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

See similar equations:

| 3(2+-0.5y)-2y=13 | | -4*7= | | 7(3+b)=-70 | | 8*3*4= | | -2(2a+3)=-6 | | (17-12)(19-9)(7-4)= | | -2(2a-3)=34 | | (17-12)*(19-9)*(7-4)= | | 7z-15=-15+4z | | 1+0.5y+y=7 | | 5n+11=-2+1 | | 4(2x-5)=3(2x+8) | | 3y-2=7 | | 3x^2+kx-18=0 | | 2y^2+6y+9=0 | | 2x+8y=1 | | -5(3x+7)=10 | | 8x^2+73x+70=0 | | 8x^2-73x-70=0 | | 7(c+4)=21 | | 10*10=x*4 | | 8x^2+73x-70=0 | | 15*16=12*x | | 8x^2-73x+70=0 | | 3*13=x*9 | | 15*10=x*5 | | 64*60= | | 3+2x+4X^2=0 | | 48*64= | | 60*80=eh*fh | | 60*80=4800 | | 60*80= |

Equations solver categories